2011
DOI: 10.1111/j.1468-3083.2011.04194.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections in pregnant adolescents: prevalence and association with maternal and foetal morbidity

Abstract: Sexually transmitted infections are frequently asymptomatic and cause maternal-foetal morbidity. The opportunity that pregnancy offers for screening and counselling should not therefore be missed, especially in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 26 publications
2
26
0
3
Order By: Relevance
“…Consistent with other studies , N. gonorrhoeae had a low prevalence of 1.3% in the pregnant women [ 26 , 27 ]. Similar to C. trachomatis , there was no significant relationship between the prevalence of N. gonorrhoeae and the mothers’ educational status and age.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other studies , N. gonorrhoeae had a low prevalence of 1.3% in the pregnant women [ 26 , 27 ]. Similar to C. trachomatis , there was no significant relationship between the prevalence of N. gonorrhoeae and the mothers’ educational status and age.…”
Section: Discussionsupporting
confidence: 92%
“…These results confirmed those obtained in the same population in a previous study performed in 2011 in the same hospital, using the cobas® 4800 CT/NG test (Peuchant et al, 2015), and are in agreement with those reported in the literature (Borges-Costa et al, 2011). Among women requesting abortion, the prevalence of C. trachomatis was 10.4% in our study.…”
Section: Discussionsupporting
confidence: 96%
“…those with many mild and asymptomatic cases of mostly self-limiting illness) and where an unknown burden exists within the community, e.g. sexually transmitted infections with Chlamydia trachomatis [36-40] or Neisseria gonorrhoea [36-39,41-44]; influenza and influenza-like illnesses [45,46]; and food and water-borne diseases [2,47-54]). The first and second Infectious Intestinal Disease studies (IID1 and IID2) were prospective community cohort studies that estimated overall incidence of infectious intestinal disease (IID) in the UK community, the proportion seeking healthcare (ascertained), and the proportion reported to the national public health agency [2,11,47,55].…”
Section: Introductionmentioning
confidence: 99%